2009
DOI: 10.1007/s12573-009-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Rheological study on coagulation of blood with special reference to the triggering mechanism of venous thrombus formation

Abstract: A markedly reduced blood flow, an elevation of hematocrit and an increased aggregability of erythrocytes [red blood cells (RBCs)] are risk factors for venous thrombus formation (intravascular blood coagulation). However, these risk factors alone seem to be insufficient to stimulate the coagulation cascade in the absence of a primary triggering mechanism. In this paper, our rheological and biochemical studies on blood coagulation, especially focusing on procoagulant activity of RBCs, are summarized. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…In Table 1, the Ti values for aged donors were smaller than those for normal young adults aged 64 years or less (Ti 31.2 ± 5.5 min [13]). The Ti value for the type II group was somewhat smaller than that for the type I group.…”
Section: Discussionmentioning
confidence: 83%
“…In Table 1, the Ti values for aged donors were smaller than those for normal young adults aged 64 years or less (Ti 31.2 ± 5.5 min [13]). The Ti value for the type II group was somewhat smaller than that for the type I group.…”
Section: Discussionmentioning
confidence: 83%
“…In this scenario, a high-shielding stent is advantageous for IA embolization but is disadvantageous for side-branch vessel flow patency. The influence of blood flow shear rate on thrombosis promotion has been reported in previous papers [10,11]; therefore, we only studied the relationship between the pore design of the shielding stent and the shear rate of IA flow [17]. Both reliable IA embolization and patency of the perforating arteries were achieved by placing MCS (NCVC-CS1) in a previous study [9].…”
Section: Discussionmentioning
confidence: 99%
“…By shielding the IA neck using a stent, blood flow entering the IA from the parent vessel is significantly reduced. Various studies have demonstrated that thrombus formation is promoted by reducing hydrodynamic parameters, especially shear rate [10,11]. Stagnation of the blood flow in the IA causes thrombosis of the entire IA area, which enables IA treatment to be accomplished via endothelialization of the stent lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that the activation of factor IX by RBCs and subsequent propagation reaction on RBC and platelet membranes are important for initiating and controlling blood coagulation reactions [20]. The ability of F-IX activated by F-IX-activating enzyme in RBC membranes to cause coagulation is low as compared with that activated by factor XI, and RBCs from different individuals differ in their capacity to activate F-IX and to promote the propagation reaction on RBC membranes [14,16,20]. In addition, it is reported that levels of fibrinogen, coagulation factors VII, VIII and IX, high molecular weight kininogen, prekallikrein and vWF are known to increase with age [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the F-IX activation by RBCs was enhanced by a decrease in the flow shear rate [15]. Therefore, we considered that this pathway suggests one route to coagulation or thrombus formation that occurs in stagnant flow regions (venous thrombus) [16].…”
Section: Introductionmentioning
confidence: 99%